EVALUATION OF THE RELATIONSHIP BETWEEN PROSTHODONTICS AND PERIODONTICS. A REVIEW - Odette-Elena Luca; Ioana Martu; Ionut Luchian; Elena Luca; Dragos Virvescu; Vladina Andronache; Monica Tatarciuc; Silvia Martu (Romanian Dental Association for Education, 2019)
This article was aimed at addressing the key relationship between prosthodontics and periodontics. The impacts of healthy periodontium on longevity of prostheses were addressed. The interdisciplinary approach has been a trend for a comprehensive dental treatment. Within modern dentistry, periodontics and prosthodontics share an intimate and inseparable relationship in multiple aspects, including treatment plan, procedures execution, outcome achievement and maintenance. By controlling inflammation and preparing sites for proper prosthetic prostheses, periodontists no doubt can provide a solid foundation for successful prosthetic outcomes. On the other hand, prosthodontists could construct proper restorative margin, shapes and contacts that benefit the harmony of periodontium and prosthesis.